Cultural Othering in Social Work. Reflections from a Critical Race Perspective - Matthias Rangger (Social Work and Society, 2025)
This paper explores the connection between diversity and client-provider relationships in social work with a focus on discourses and practices of cultural othering. To pursue this topic, the paper discusses empirical data from a training series held in Germany on pedagogical professionalism in a society which is constitutively produced and structured by migration phenomena. From the theoretical perspective of cultural othering the paper highlights three ideal types of reference to "cultural diversity" in social work practice and its effects: "domination","recognition" and "agency", which express the fundamental power and contradictory nature of social work in general. The paper concludes with an"othering-reflective" approach that takes full account of the complexity and contradictoriness of social work in the contexts and conditions of social inequality.